The Effect of Halal Labeling and Lifestyle on Purchasing Decisions with Purchase Intention as a Mediating Variable - Yochi Elanda; Muhammad Ramadhan; Isnaini Harahap (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Consumer awareness of halal and lifestyle trends increasingly shapes purchasing behavior in the cosmetics industry. This study analyzes the influence of halal labeling and lifestyle on purchasing decisions cosmetic products, with purchase intention as an intervening variable. The research aims to understand how these factors drive consumer behavior in Medan City. A quantitative survey was conducted among 207 consumers selected using accidental sampling based on Slovin’s formula. Data were collected via questionnaires and analyzed using SEM-PLS with SmartPLS. The results indicate that both halal labeling and lifestyle positively and significantly affect purchase intentions. Lifestyle also directly influences purchase decisions, whereas halal labeling does not, although it indirectly affects decisions through purchase intention. Purchase intention significantly mediates the relationship between lifestyle and purchasing decisions, but not between halal labeling and purchasing decisions. The study highlights that aligning products and marketing with consumer lifestyle trends, such as natural ingredients and eco-friendly practices, is crucial. Providing clear and informative halal labeling remains important to build trust and stimulate purchase intention, even if it does not directly drive buying decisions.